Urographic examination using non-ionic contrast media - Arif Faisal Arif Faisal (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1992)
Non-ionic (Iopamiro) and ionic (Urografin 76%) contrast media were used for intravenous urographic examination. Three patients (6%) showed symptoms of side effect in ionic group; two of them without allergy history, but only one patient had an experience of allergy to shrimp, penicillin and dust. The symptoms of reaction were chills, dizziness and febris.There was no reaction in non-ionic group patients. The density of contrast media was superior in using Iopamiro.Key Words : intravenous urography - Iopamiro - Urografin 76% - allergy - radiology